2014
DOI: 10.1017/s0033291714002530
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of preventing first-episode psychosis in ultra-high-risk subjects: multi-centre randomized controlled trial

Abstract: Add-on preventive CBT for UHR resulted in a significant reduction in the incidence of first psychosis. QALY gains show little difference between the two conditions. The CBT intervention proved to be cost saving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 38 publications
1
69
2
Order By: Relevance
“…35,[38][39][40][41] The cost-effectiveness plane in this study at 48-month follow-up was further improved compared with the 18-month follow-up. This study showed that CBTuhr had an 83% likelihood of resulting in a reduction of the transition to psychosis at a lower cost.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…35,[38][39][40][41] The cost-effectiveness plane in this study at 48-month follow-up was further improved compared with the 18-month follow-up. This study showed that CBTuhr had an 83% likelihood of resulting in a reduction of the transition to psychosis at a lower cost.…”
Section: Resultsmentioning
confidence: 53%
“…Also from the societal perspective, there is a substantial likelihood (73% in the primary and 78% in the secondary analysis) that CBTuhr results in more effects at lower costs. The conclusions indicate that the results of the 18 months analysis 35 do not deteriorate when considering a period of 4 years and guided some patients through a critical period with declining transition rates. 36 …”
Section: Main Findingsmentioning
confidence: 83%
See 2 more Smart Citations
“…Ising et al [14] studied the cost-effectiveness and cost utility of CBT in the prevention of first-episode psychosis. In this multicenter trial, 196 ultra-high-risk (as determined by the Comprehensive Assessment of At-Risk Mental States - CAARMS) were assigned to either routine care (101 subjects) or to routine care plus add-on individual CBT aiming at the prevention of a first episode of psychosis (95 subjects).…”
Section: Early Intervention and Preventionmentioning
confidence: 99%